Race, Power, Privilege, A Critical Analysis of Systematic Racism - Rashed Ahmed (MANDALIKA : Journal of Social Science, 2026)
This paper critically analyzes complex interactions between power, privilege, and race in the context of institutionalized racism, highlighting the structural and historical dimensions of racial disparities that continue to perpetuate racial inequality. Based on a comprehensive review of the literature and an online search, the study examines how power relations benefit majority racial groups, privilege is exercised as an unseen benefit, and institutionalized racism extends to a range of societal institutions, such as schools, hospitals, workplaces, and the criminal justice system. One of the most important findings of this study is that systemic racism is historically entrenched. It was colonialism, slavery, and institutional discrimination that created foundations for racial hierarchies that continue to influence contemporary power dynamics. These historical injustices have become ingrained in legal systems, policy, and societal norms, therefore resulting in long-lasting inequalities. The research also uncovers the role of privilege in sustaining these disparities. Privilege allows certain racial groups to live life with unearned advantages, at times even without their owners' knowledge, while marginalized groups face perpetual obstacles. This privilege encompasses access to education, economic opportunities, and equal treatment under the law, sustaining cycles of disadvantage.